Determination of phytoplankton density, and study of the variation of nutrients and heavy metals in the surface water of Riva Stream; one of the water sources of Istanbul, Turkey - ÖZYİĞİT, İBRAHİM İLKER (TAYLOR & FRANCIS INC, 2015)
In this study, the water quality and heavy metal pollution status of Riva Stream which is related to omerli Dam Lake, one of the water resources of Istanbul (Turkey), was determined. For this purpose, some physicochemical parameters, phytoplankton compositions, some nutrient, and heavy metal concentrations in the surface water of Riva Stream were investigated. Samples were collected at six sampling sites in the course of the stream in February 2012 and May 2012. A total of 19 taxa, belonging to five divisions, were identified. The phytoplankton density varied from 47 to 264ind./cm(3); chlorophyll-a contents varied between 1.52 and 1.83mg/m(3). Measured concentrations of heavy metals and nutrients showed difference related to sampling points. As a result of measurements, the lowest and highest heavy metal and mineral nutrient concentrations of measured water samples were as follows: Al (617.40-1094.16g/L), B (1010.40-5736.00g/L), Ca (1015.80-1925.40mg/L), Cd (1.45-5.22g/L), Cr (61.26-164.16g/L), Cu (35.04-372.66g/L), Fe (28.50-369.06g/L), K (179.10-1314.60mg/L), Mg (202.68-1755.60mg/L), Na (669.00-1553.40mg/L), Ni (40.62-269.70g/L), Pb (6.48-76.86g/L), and Zn (429.18-990.60g/L). It was observed that Riva Stream is highly polluted by some heavy metals, and a number of heavy metal resistant/tolerant phytoplankton species are present in the stream. Pearson's correlation and Spearman rank correlation analyses were applied to examine the relationship between Al, B, Ca, Cd, Cu, Cr, Fe, K, Mg, Na, Ni, Pb, Zn, pH, chlorophyll-a, salinity, and conductivity. The physicochemical characteristics of Riva Stream as a high concentration of nutrients make it a similar eutrophic. It is required that, Riva Stream should be taken under protection as soon as possible for improving its water quality by relevant authorities.
Keywords: Phytoplankton; Trace elements; Nutrients; Physicochemical parameters; Chlorophyll-a; Istanbul; POLLUTION; CONTAMINATION; RUSSIA; REGION; SOILS; FISH